Incorporating Unstructured Socializing Into the Study of Secondary Exposure to Community Violence: Etiological and Empirical Implications. (July 2014) - Zimmerman, Gregory M.; Messner, Steven F.; Rees, Carter
Secondary exposure to community violence, defined as witnessing or hearing violence in the community, has the potential to profoundly impact long-term development, health, happiness, and security. While research has explored pathways to community violence exposure at the individual, family, and neighborhood levels, prior work has largely neglected situational factors conducive to secondary violence exposure. The present study evaluates "unstructured socializing with peers in the absence of authority figures" as a situational process that has implications for secondary exposure to violence. Results indicate that a measure of unstructured socializing was significantly associated with exposure to violence, net of an array of theoretically relevant covariates of violence exposure. Moreover, the relationships between exposure to violence and three of the most well-established correlates of violence exposure in the literature—age, male, and prior violence—were mediated to varying degrees by unstructured socializing. The results suggest a more nuanced approach to the study of secondary violence exposure that expands the focus of attention beyond individual and neighborhood background factors to include situational opportunities presented by patterns of everyday activities.